Rapid weight loss and mood states in judo athletes: A systematic review - Lakicevic, Nemanja; Thomas, Ewan; Isacco, Laurie; Tcymbal, Antonina; Pettersson, Stefan; Roklicer, Roberto; Tubic, Tatjana; Paoli, Antonio; Bianco, Antonino; Drid, Patrik (European Review of Applied Psychology-Revue Europeenne De Psychologie Appliquee, 2024)
Objective: Rapid weight loss (RWL) has been traditionally practiced in judo. While the effects of it on performance and health have been extensively studied, less attention is dedicated to psychological ramifications of RWL. We sought to investigate the effects of RWL on mood states in judo athletes. Method: PubMed and Web of Science were systematically searched for the relevant literature. Only original studies investigating the magnitude of RWL in judo athletes while jointly using Profile of Mood States questionnaire were eligible. Results: Six studies met the inclusion criteria and were included in the analysis. Studies varied vastly in their design (time allocated to RWL and the degree of RWL), but the common trait in virtually all studies was a significant increase in tension and significant drop in vigor following RWL. It appears that when ≥ 5% RWL per week is prompted, mood states greatly exacerbate in judo athletes. Conclusion: Overall, data showed that mood states in judo athletes are aggravated after ≥ 5% RWL with no significant difference between males and females. Future studies should explore the long-term effects of weight cycling on the mental health of judo athletes and other athletes participating in weight-classified sports.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Anger; Confusion; Depression; Fatigue; Mood states; Tension; Vigor; Weight cycling